(untitled) (Nepal Journal of Epidemiology, 2010)
Background Youth is a vulnerable group for developing almost all life-style related diseases. The present cross-sectional study was conducted to assess the determinants of blood pressure among entry year students in a medical university in Ajman, United Arab Emirates. Materials and Methods One hundred and ten students from Gulf Medical University, Ajman, UAE participated in the study. A pretested structured questionnaire was used for data collection. Predictive Analytic Software 17 was used for data analysis. Chi-square test, Univariate and multivariate logistic regression were used. Results Variables such as tobacco use, duration of sleep, Body Mass Index and gender were considered to assess the association with blood pressure. The mean age of the students was 19 years with a SD of 1.9 years. The mean systolic and diastolic blood pressure was 113.5 (SD 12.0) and 73.7 (SD 11.2) respectively with mean BMI of 24.9 (SD 5.7). A statistically significant association was observed between gender and blood pressure (p<0.05). The crude Odds Ratio (OR) observed for sleep duration and blood pressure was found statistically significant (p<0.05), but the adjusted OR was not statistically significant. Of the participants who sleep for more than 6 hours, majority (70%) have normal blood pressure. Nearly half of the participants who slept for less than 6 hours have pre-hypertension and/ or hypertension. There was statistically significant (p<0.005) association between Body Mass Index (BMI) and blood pressure (BP). The mean BMI among those with normal BP was 23.25 kg/m2 with a SD of 4.6 and those with pre-hypertension and/ or hypertension was 27.6 kg/m2 with a SD of 6.5. Conclusion Gender and BMI are the significant factors associated with Blood pressure. The findings may be used to create strategies to impart awareness of the dangers of increased blood pressure among obese and non obese students. Key Words: Body Mass Index; Blood Pressure; UAE DOI: 10.3126/nje.v1i1.4107 Nepal Journal of Epidemiology 2010;1 (1):17-21